2020
DOI: 10.3390/antibiotics9090597
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Practice of Self-Medication with Antibiotics among the Lay Public in Low- and Middle-Income Countries: A Scoping Review

Abstract: The current scoping review is an attempt to explore the key reasons, determinants, patterns and prevalence related to self-medication with antibiotics (SMA) among the lay public. An online search was conducted using Google Scholar, Science Direct, ProQuest and PubMed. A two-phase mapping approach was used. In the first phase, studies were screened. In the second phase, the data were extracted from selected studies followed by the assessment of data quality. A total of 24 studies were included; 20 were cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 47 publications
7
95
1
5
Order By: Relevance
“…Several other factors were also associated with taking antibiotics for preventative purposes and were largely consistent with those that have been identified as key determinants of self-medication with antibiotics in previous studies [11,15,31,32,34,35]. First, a lack of knowledge about antibiotics was shown to be quite common among the Australian public, and in some instances, this lack of knowledge was significantly associated with taking antibiotics for COVID-19.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Several other factors were also associated with taking antibiotics for preventative purposes and were largely consistent with those that have been identified as key determinants of self-medication with antibiotics in previous studies [11,15,31,32,34,35]. First, a lack of knowledge about antibiotics was shown to be quite common among the Australian public, and in some instances, this lack of knowledge was significantly associated with taking antibiotics for COVID-19.…”
Section: Discussionsupporting
confidence: 84%
“…Tackling AMR has become an urgent priority for policy makers globally [14]. Research so far has suggested that self-medication with antibiotics is often caused by a lack of knowledge about antibiotics, widespread availability of antibiotic medications due to absence of government regulations and enforcement, and incorrect practices such as not completing the full treatment course and keeping the remaining antibiotic medications [15][16][17][18]. These insights have informed the design of campaign strategies globally in managing antibiotic misuse, wherein the focus is on education and dissemination of knowledge [19][20][21][22].…”
Section: Antimicrobial Resistance and Self-medication With Antibioticsmentioning
confidence: 99%
“…A recent scoping review highlighted the self-medication of antibiotics to be highly prevalent among individuals living in low- and middle-income countries. 45 Such medications are often connected with improper use as fever, upper respiratory tract infection, common cold and sore throat. Information about antibiotics were mainly provided by pharmacists or a family member.…”
Section: Development Of Abr In Clinical Practice: the Role Of Inappromentioning
confidence: 99%
“…Colistin (COL) is one of the few last-line antibiotics used in treating deadly infections caused by multidrug-resistant (MDR) and extensively drug-resistant (XDR) Gram-negative bacilli (GNB). The unrestricted use of antibiotics in human medicine, especially in form of self-medication that is predominant in low and middle-income countries, is a major cause of development of antimicrobial drug resistance [ 1 ]. The use of COL in humans was largely abandoned in the 1970s due to its neurotoxic and nephrotoxic effects alongside to the discovery and approval of new and effective antibiotics [ 2 ], but COL has been used in livestock for more than six decades in most countries in the world, including Africa [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%